ANALYSIS ON THE TRANSLATION STRATEGIES OF POPULAR DISNEY SONG LYRICS: Analisis Strategi Penerjemahan Lirik Lagu-Lagu Populer Disney - Hardwi Atmaja, Hernandez Trivano; Naila Rohmah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study examines translation strategies used in the Indonesian versions of ten popular Disney songs, in response to the growing importance of culturally resonant translations in global media. With over 2.5 million Disney+ Hotstar users in Indonesia, localized song lyrics play a key role in enhancing audience engagement. Using a descriptive qualitative method and documentation analysis, this research analyzes English and Indonesian lyrics of songs such as Let It Go, A Whole New World, and Beauty and the Beast. Findings show paraphrasing as the most frequently used strategy (165 instances), followed by adaptation and substitution (59 each), omission (25), and addition (2). These results highlight how translators prioritize meaning and musicality in Indonesian renditions. The study concludes that song translation requires balancing semantic accuracy, rhythm, and cultural context. The findings contribute to a deeper understanding of audiovisual translation in multilingual and multicultural contexts. Future work may explore similar strategies across other languages and media platforms.